If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1x + -12 = 0 Reorder the terms: -12 + 1x = 0 Solving -12 + 1x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + 1x = 0 + 12 Combine like terms: -12 + 12 = 0 0 + 1x = 0 + 12 1x = 0 + 12 Combine like terms: 0 + 12 = 12 1x = 12 Divide each side by '1'. x = 12 Simplifying x = 12
| t+.472=8.9 | | 9x^5y^3+45x^3y^2+27xy=0 | | -(-6)=x | | 7y^8-7y^4=0 | | -1+9w=9 | | 2w-7=-2 | | x+x-6x+6=0 | | 9w+4=3 | | 2v+17= | | 4x+5(40-x)=160 | | x=-4x^2-8x+4 | | x=-x^2+5x+2 | | 3(4x-1)= | | 8k^2=k^5 | | (4-u)(4u-6)=0 | | -7=8z-2 | | 6t^2-60t+126=0 | | -(x-18)+2(x+3)=6(x+4) | | -3n=6(6-n) | | 3x^2+28x=-60 | | 2y=-5(y+1) | | 5k^2=-80 | | -9+5y=-9 | | 5(y-3)=4y | | 8x=4(x+5) | | -(7y+4)-(-6y-5)=-3 | | 4(n-2)=-8 | | 5Z+5=-3 | | 1.6r+7=1.2r+15 | | 9(2x-2)=3(6x+4) | | -7y+22=3y-8 | | 4+9p-2=8p+23-6p |